Perlindungan Hukum Terhadap Pemegang Hak Atas Merek Dari Perbuatan Pemboncengan Reputasi (Passing Off)> Legal Protection for Brand Holder from Passing off - Perpustakaan UGM, i-lib ([Yogyakarta] : Sekolah Pascasarjana Universitas Gadjah Mada, 2003)
ABSTRACTThis research is a juridical research which aims to obtain a description of a brand related passing off and to study legal protection for brand holder from a passing off action.The research is conducted by using a library research and field research in Jakarta District Capital. The background of choosing the research location is that it is the center of government as well as the development, making it referred as the barometer for the implementation of brand protection. Besides, it houses the institutions dealing with brand protection. The method for collecting the data is a non-probability sampling technique and for determining the sample is a purposive sampling technique in which the determination is based on a particular purpose or consideration.The research results show that the Law provides legal protection for a brand holder from a passing off action by means of both preventive and repressive measures in accordance with the legal terms, which are both general and specific in nature, while observing the limitations. Besides having its legal terms, a sufficient protection insists on law enforcement which, in reality, shows problems in relation to the rule of law, culture, economic condition and capacity of the law enforcing apparatus.